Public green spaces and management constraints in the Municipality of Seme-Podji South East of Benin - FANGNON, BERNARD (My University, 2021)
An increasingly present component in urban architecture, public green spaces is an essential infrastructure that has various functions. The management of these spaces poses enormous difficulties after their establishment. The study has analyzed the uses and management of these spaces in the Municipality of Sèmè-Podji. It was carried out on the basis of a sample of 84 people made up of users and managers of green spaces, heads of neighborhoods or villages, heads of districts and officials of the Technical Services Department of the Town Hall. The thirty-three (33) green spaces still functional in the Municipality were visited. These are unevenly distributed between the districts and that of Agblangandan has the largest number (12). The density of green space in Sèmè-Podji was 0.132 green space/km2 in 2018 against 0.02 in 2017, which remains low. Very frequented by young people (58.15%), the green spaces serve as places of leisure, rest, maintenance sports and are home to small shops. They are managed by the town hall, by local elected officials, or entrusted to individuals who, in return, pay royalties to the municipality. Poor infrastructure coverage and maintenance which generates visual and olfactory pollution according to 97.94 and 86.90% of the target population. Besides, the lacks of innovation in the activities offered to the public are the main constraints to the management of green spaces in the Municipality of Sèmè-Podji.
Keywords: Sèmè-Podji; public green spaces; management; constraints